2018
DOI: 10.22159/ajpcr.2018.v11s1.26577
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Counseling on the Management of Patients With Type 2 Diabetes Mellitus Admitted to a Hospital

Abstract: Objective: The objective of the study was to study the impact of counseling on costs and effectiveness of type 2 diabetes mellitus (T2DM) outpatients in An-Nisa Hospital, Tangerang, Indonesia, period July 2016 to November 2016.Methods: This 4-month prospective quasi-experimental study was undertaken to analyzed the impact of counseling on cost and effectiveness in the treatment of patients with T2DM (n=30). The cost analysis was conducted from the perspective of Badan Penyelenggara Jaminan Sosial abbreviated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
1
0
2
Order By: Relevance
“…The present study found that 66.7% of the patients were female. This finding supported similar studies undertaken in Indonesia and USA [13], [14], [15]. It was indicated that 56% of the T2DM patients were at the age of 60 years or above.…”
Section: Discussionsupporting
confidence: 91%
“…The present study found that 66.7% of the patients were female. This finding supported similar studies undertaken in Indonesia and USA [13], [14], [15]. It was indicated that 56% of the T2DM patients were at the age of 60 years or above.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the CEA as shown in Table 12, ICER calculation was not necessary because the typical antipsychotic has low effectiveness with high costs, so it did not need to be considered as an alternative, and atypical antipsychotics had high effectiveness with lower costs so it was definitely chosen and not needed ICER calculation. Based on these data it can be concluded that atypical antipsychotics were more cost effective than typical antipsychotics [5], [10]- [13].…”
Section: Calculation Of the Effectiveness Of The Cost Of Using Antipsmentioning
confidence: 91%
“…Secara fisik, perempuan memiliki peluang lebih besar dalam peningkatan indeks massa tubuh, sindrom siklus bulanan (premenstrual syndrome), dan pasca menopause yang membuat distribusi lemak menjadi lebih mudah terakumulasi dalam tubuh sebagai hasil dari proses hormonal. Oleh karena itu, prevalensi DM pada perempuan lebih tinggi dibandingkan laki-laki (4,13).…”
Section: Karakteristik Pasien Dm Tipeunclassified
“…Berdasarkan Riskesdas 2018, prevalensi DM menunjukkan peningkatan seiring dengan bertambahnya usia penderita yang mencapai puncaknya usia 55 sampai 64 tahun dan menurun setelah melewati rentang usia tersebut (4,14). Pada dasarnya dalam mengontrol gula darah tergantung dari kesadaran dan kepatuhan individu melalui life style (13,15). Kurangnya aktivitas fisik juga menyebabkan toleransi tubuh terhadap glukosa dan sensitivitas tubuh terhadap insulin semakin berkurang, sehingga hal tersebut dapat menyebabkan orang yang tidak bekerja, seperti ibu rumah tangga, memiliki aktivitas fisik yang kurang dan mengakibatkan tubuhnya kurang sensitif terhadap insulin (16).…”
Section: Karakteristik Pasien Dm Tipeunclassified